The Effect of Distance Learning on Children's Moral Development - Hermawati, Wanda Alifah; Giva Salsabilla, Heidi; Rustini, Tin; Wahyuningsih, Yona (Universitas Muhammadiyah Yogyakarta, 2022)
Moral is the foundation of a person when behaving and carrying out his role in society. In today's digital era, we can see a lot of decline in the values and morals that used to be embraced by society. Advances in the digital field do not necessarily bring moral to a more advanced level, especially during this pandemic which also exacerbates moral decline. The lack of direct interaction during learning makes students indifferent to moral values. The decline in the